2003
DOI: 10.1021/jp0348934
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Platinum on Nanometer-Sized Carbon Electrodes

Abstract: Results for the electrodeposition of platinum on carbon electrodes of nanometer size are presented. It is shown that electrodes with very small electroactive areas simplify the study of the nucleation and growth mechanism involved in electrodeposition. Reducing the electroactive area of the substrate easily controls the number of nucleation sites. With the use of substrates having electroactive radii of a few nanometers, it is possible to form only one single growth center and to allow that center to grow inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
168
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(179 citation statements)
references
References 38 publications
3
168
1
7
Order By: Relevance
“…Thus, in principle, for r approaching 10 nm, interfacial rate constants exceeding 1 cm s À1 should be measurable. Again, formation of nanometre scale L/L interfaces has parallels with analogous work on the formation of ''nanoelectrodes'' using nanometre scale objects to define disc- 34,35 or band-shaped electrodes. 36 On the nanometre scale, a key issue becomes the fidelity of the interface: over this length scale, how reproducibly can we construct a conducting surface?…”
Section: Ion Transfer At the Modified L/l Interface: Mesoporous Matermentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, in principle, for r approaching 10 nm, interfacial rate constants exceeding 1 cm s À1 should be measurable. Again, formation of nanometre scale L/L interfaces has parallels with analogous work on the formation of ''nanoelectrodes'' using nanometre scale objects to define disc- 34,35 or band-shaped electrodes. 36 On the nanometre scale, a key issue becomes the fidelity of the interface: over this length scale, how reproducibly can we construct a conducting surface?…”
Section: Ion Transfer At the Modified L/l Interface: Mesoporous Matermentioning
confidence: 97%
“…102 Studies of the deposition of metals on (solid) electrode surfaces have used microelectrodes in an attempt to reduce the number of nucleation sites toward one, and thereby simplify the analysis of the associated current response by eliminating the need to consider the overlap between multiple diffusion fields. 35,103 The study of silver deposition at the pipette-defined water/ DCE interface included some SEM of the deposits, which again suggested that the deposits were on the micron scale. Importantly this communication also provided a preliminary comparison of electrochemical and structural (SEM) data, suggesting that around seven silver nuclei were formed in a two micron radius pipette, 102 although it is not immediately clear if deposit aggregation can be distinguished from the formation of individual nuclei.…”
Section: Ion Transfer At the Modified L/l Interface: Mesoporous Matermentioning
confidence: 99%
“…For instance, in platinum black that comprises platinum particle aggregates and has a porous structure, the effect of temperature [1] and additives [10][11][12][13][14] on the size of particle was investigated. No platinum particle aggregates at an initial growth stage developed into a dense thin film with a small surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction process of a platinum atom from a Pt(IV) ion analyzed by cyclic voltammetry was proposed as the following equation [13,16]:…”
Section: Introductionmentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11][12][13] However, as the vast majority of investigations have employed a large number of particles in a catalytic ensemble, the information obtained is limited due to unavoidable variations in NP size, shape and local environment. 14 Efforts to circumvent this limitation have been made by shifting to single particle measurements, [15][16][17][18][19][20] but such studies are rather challenging. 21 In general, single particle experiments fall into one of two categories.…”
mentioning
confidence: 99%